The Influence of a Cloud-Based Enterprise Resource Planning System and Organization IT Strategy on Business Operational Efficiency through the Warehouse Management Process: a Case Study of the Automotive Parts Industry in Thailand - Srisawat, Jakraphun (NIDA Business Journal, 2025)
This research aimed to study the impact on the operational efficiency. Independent variables were the utilizing of ERP Cloud Base system and information technology strategy, while warehouse management was the mediating variable. Dependent variable was the operational efficiency. Sample consisted of 215 people involved in the organization's information system, including executives, information technology executives, information technology managers, and information operation officers, selected from the automotive parts industry via stratified random sampling method. Data were analyzed using the Structural Equation Model (SEM), which the model structure was applied to test the hypothetical model. Results indicated that the model had proportion and all hypotheses regression were accepted with p-value < 0.05. The results of the fit and consistency test were consistent with the empirical data and sub-components of the structural model, Research results showed that using ERP Cloud Base system and information technology strategy had direct impact on the operational efficiency. In addition, indirect impact was also shown in warehouse management, indicating that ERP Cloud Base system and information technology strategy implementation should combine with appropriate warehouse management in order to further improve the organization’s operational efficiency.